Financial Implementation of Digital Wallet Halal Development on Generation Z's Shopping Intention on Food Products - Saraswati, Ety; Rachmadi, Kartika Rose (ITB AAS INDONESIA Surakarta, 2024)
The study of halal consumption is very important because the halal market is booming and has practical policy implications for stakeholders (such as marketing managers, government and corporate vision). Therefore, this study explores the determinants of the purchase intention of halal products that have been certified among Muslim minority countries in Russia because of the low attention of researchers in the study. So far a lot of research on this issue has focused on Muslim-majority countries. The purpose of this study is to conduct empirical studies by analyzing empirical models of Halal awareness, Halal certification, Halal marketing, Halal habit, Halal knowledge and religious belief in consumers' intention to buy products that are halal certified among Russian consumers. Using a quantitative approach and non-probability sampling design, this study explores information from 216 respondents in one of the important cities in the Siberian region of Russia. From the collected data, 204 respondents were declared complete, then validity tests (correlation of person product moment) and reliability (cronbach alpha) were carried out for further classical assumption test analysis (normality, multicollinearity, heteroscedasticity and autocorrelation test) to determine data quality. Based on multiple linear regression analysis, information obtained that Halal Knowledge and Religious belief significantly influence consumers' intention to buy products that are halal certified among Russian consumers. Surprisingly Halal awareness, Halal certification / logo, Halal marketing and Halal habit have no effect on their intentions. Finally, Russian consumers believe that consuming halal products is due to their religious encouragement and knowledge of halal products. Marketers need to design a unique strategy to convince consumers that products circulating in the Russian market are halal products that are in accordance with Islamic sharia and meet Russian halal certification standards.